2016
DOI: 10.1007/s11069-016-2210-7
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward disaster-prevention risk in Japanese coastal areas: analysis of civil preference

Abstract: Facing potential coastal disasters such as storm surges, storm waves, and tsunamis, Japan has planned the construction of coastal structures such as seawalls or breakwaters along its coastal areas. However, some conflicts exist among the public whether such constructions should be undertaken or whether the natural coast should be conserved. This study uses a choice experiment to investigate opinions of coastal citizens about (1) the acceptable loss of coastal wildlife species as a tradeoff for seawalls; (2) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Choice experiments, which are one of the stated preference methods, allow researchers to consider the tradeoffs among ESSs [50,51]. Thus, choice experiments have been recently applied to coastal research [46,52], providing information regarding some changes in coastal settings and asking their most preferred options. Following this trend, this project applied choice experiments to clarify people's preferences toward coastal ESSs and their tradeoffs by jointly considering several important attributes for different hypothetical coastal settings (Figure 3).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Choice experiments, which are one of the stated preference methods, allow researchers to consider the tradeoffs among ESSs [50,51]. Thus, choice experiments have been recently applied to coastal research [46,52], providing information regarding some changes in coastal settings and asking their most preferred options. Following this trend, this project applied choice experiments to clarify people's preferences toward coastal ESSs and their tradeoffs by jointly considering several important attributes for different hypothetical coastal settings (Figure 3).…”
Section: Experimental Designmentioning
confidence: 99%
“…A study conducted in New Jersey found that in coastal people's perceptions of coastal infrastructure, nature-based approaches (i.e., wetlands and dunes) are preferable to gray infrastructure (revetments and groins) [45]. In particular, people in Japan who frequently visit the sea prefer to conserve the shoreline, which provides multiple ESSs [46].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature of environmental valuation, several studies using the stated preference approach try to understand preferences over uncertain outcomes (Roberts et al 2008). There are several studies that use discrete choice experiments in this context (Glenck and Colombo 2013;Imamura et al 2016;Glatte et al 2019). Imamura et al (2016) examined people's attitudes toward disaster-prevention risk in coastal areas using a discrete choice experiment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the standpoint of disaster management, mitigating the impact of future tsunamis by building embankments is essential. The government has already invested several hundred billion yen in dike construction around disaster areas (Ishiwatari and Sagara, 2012;Imamura et al, 2016). Badly damaged prefectures such as Fukushima, Miyagi, and Iwate have been constructing dikes and increasing the height, width, and in some cases the length of seawalls since the disaster.…”
Section: Building Embankmentsmentioning
confidence: 99%